Pola Pengobatan Coronavirus Disease-19 (COVID-19) dengan Komorbiditas Tuberkulosis Paru Pada Pasien Rawat Inap RSUD Al-Ihsan Bandung Tahun 2020 - Chanief Hassan Widjaja; Novita Carolia; Intanri Kurniati (Medula, 2023)
Coronavirus disease-19 (COVID-19) is an infectious disease caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) and attacks the respiratory tract as its main target. Pulmonary tuberculosis (TB) is a disease with high incidence in Indonesia and transmitted through the respiratory tract and attacks lung organs same as COVID-19, allowing the possibility for co-infection of the two microorganisms simultaneously. The purpose of this study was to determine the pattern of treatment for COVID-19 and pulmonary TB at inpatient care facility Al-Ihsan Hospital Bandung. This study was an observational descriptive study with retrospective approach. The number of samples were 15 who had COVID-19 and pulmonary tuberculosis, taken from March until December 2020 at inpatient care facility Al-Ihsan Hospital Bandung. The sample taken using the total sampling technique, then analyzed using univariate test.There are five types of drugs found in this study, which is antibiotics, anti-tuberculosisdrugs, antivirals, corticosteroids, and vitamins. The types of antibiotics used were azithromycin (80%), levofloxacin (80%), ceftazidime (13.33%), ofloxacin (6.67%), and cefotaxime (6.67%). Anti-tuberculosis drugs with fixed dose combination (FDC) were given to 13 samples (86.67%). The types of antiviral drugs used were isoprinosine (80%), oseltamivir (13.33%), and chloroquine (6.67%). The types of corticosteroid drugs used were dexamethasone (33.33%) and bethametasone (6.67%). Types of vitamins used were vitamin C (100%), vitamin B6 (6.67%), vitamin D (73.33%), and zinc supplements (33.33%).